Feed efficiency metrics in growing pigs. Issue 7 (1st July 2017) - Calderón Díaz, J. A.; Berry, D. P.; Rebeiz, N.; Metzler-Zebeli, B. U.; Magowan, E.; Gardiner, G. E.; Lawlor, P. G.
ABSTRACT: The objective of the present study was to quantify the interrelationships between different feed efficiency measures in growing pigs and characterize pigs divergent for a selection of these measures. The data set included data from 311 growing pigs between 42 and 91 d of age from 3 separate batches. Growth-related metrics available included midtest metabolic BW (BW 0.75 ), energy intake (EI), and ADG. Ratio efficiency traits included energy conversion ratio (ECR), Kleiber ratio (ADG/BW 0.75 ), relative growth rate (RGR), residual EI (REI), and residual daily gain (RDG). Residual intake and gain (RIG; i.e., a dual index of both REI and RDG) and residual midtest metabolic weight (RMW) were also calculated. Simple Pearson correlations were estimated between the growth and feed efficiency metrics. In litters with at least 3 pigs of each sex, pigs were separately stratified on each residual trait as high, medium, and low rank. Considerable interanimal variability existed in all metrics evaluated. Male pigs were superior to females for all metrics ( P < 0.001) except for both BW 0.75 and EI, where no sex differences were evident. Feed efficiency metrics improved as birth BW increased ( P < 0.05) except for RGR, where the contrary was observed. Correlations between most growth and feed efficiency metrics were strong to moderate ( P < 0.05). Low-REI pigs (i.e., more efficient) had lower EI and ECR and were superior for RIG ( P < 0.001) compared with high- and medium-REI pigs. High-RDG pigs (i.e., more efficient) had greater BW gain and better ECR ( P < 0.001) compared with medium- and low-RDG pigs. Residual EI and RIG were both superior ( P < 0.001) in high-RDG pigs compared with medium- and low-RDG pigs. Energy conversion ratio, REI, and RIG were superior ( P < 0.05) in high-RMW pigs (i.e., more efficient) compared with medium-RMW pigs. High-RIG pigs (i.e., more efficient) had lower EI ( P < 0.01) and superior ECR for RDG and REI compared with medium- and low-RIG pigs. In general, most of the correlations among the feed efficiency traits investigated in this study were different from unity, indicating that each trait is depicting a different aspect of efficiency in pigs, although the moderate to strong correlations suggest that improvement in one trait would, on average, lead to improvements in the others. Pigs ranked as more efficient on residual traits such as REI consumed less energy for a similar BW gain, which would translate into an economic benefit for pig producers.